Sistem Pendukung Keputusan Dengan Menggunakan Metode Simple Additive Weighting pada Excelso Coffee Rinjani Semarang - Lenny Ariyanto; Petrus Sokibi; Viar Dwi Kartika (UNIVERSITAS RAHARJA, 2024)
Excelso coffee is a cafe located in several cities, including in Semarang which began operating in 2017. The process of selecting raw material suppliers that is currently underway still uses the conventional method, which does not have a method for selecting suppliers. With this problem, it is expected to be able to find out the factors in the selection of suppliers of non-coffee food and beverage raw materials to make a Decision Support System Application (DSS) using the Simple Additive Weighting (SAW) method. DSS is a method used to support decision making using data, with an easy display for users, and involves the thoughts of decision makers. SAW is a method by calculating a weighted sum to rate all options and attributes. The results of this study show that the factors used in the selection of raw material suppliers are delivery speed, price, discount rate, service, warranty, product authenticity, payment term. In addition, a decision support system application is also produced which consists of a homepage menu, goods, suppliers, criteria, sub criteria, weights, ratings and results. This application can produce the best alternative recommendations according to the weight and value desired by Excelso Coffee Rinjani Semarang.